Frontier women and their art : a chronological encyclopedia - Snodgrass, Mary Ellen (Rowman and Littlefield, 2018)
This is a chronology of creative contributions made by women dating from the 1790s to 1900. Among the arts covered in this volume are quilting, beadwork, dancing, diaries and memoirs, folk music, landscaping, sculpture, theatrics, etc. Entries are cross-referenced and include further readings drawn from an exhaustive bibliography of sources.